Endothelial nitric oxide synthase in hypoxic newborn porcine pulmonary vessels. Issue 1 (1st July 1997) - Hislop, A A; Springall, D R; Oliveira, H; Pollock, J S; Polak, J M; Haworth, S G
Abstract : AIMS: To determine if the failure of neonatal pulmonary arteries to dilate is due to a lack of nitric oxide synthase (NOS). METHODS: A monoclonal antibody to endothelial NOS was used to demonstrate the distribution and density of NOS in the developing porcine lung after a period in hypobaric hypoxia. Newborn piglets were made hypertensive by exposure to hypobaric hypoxia (50.8 kPa) from < 5 minutes of age to 2.5 days of age, 3–6 days of age or 14–17 days of age. A semiquantitative scoring system was used to assess the distribution of endothelial NOS by light microscopy. RESULTS: NOS was present in the arteries in all hypoxic animals. However, hypoxia from birth caused a reduction in NOS compared with those lungs normal at birth and those normal at 3 days. Hypoxia from 3–6 days led to a high density of NOS compared with normal lungs at 6 days. Hypoxia from 14–17 days had little effect on the amount of NOS. On recovery in room air after exposure to hypoxia from birth there was a transient increase in endothelial NOS after three days of recovery, mirroring that seen at three days in normal animals. CONCLUSIONS: Suppression of NOS production in the first few days of life may contribute to pulmonary hypertension in neonates.